Comparison of five silo type for corn silage production - Nazli, Muhamad Hazim; Abdul Halim, Ridzwan; Samsudin, Anjas Asmara @ Ab Hadi; Abdullah, Amin Mahir; Hussin, Ghazali (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The type and design of silos have significant influence on the ensilation process as well as quality of silage produced. It is important to choose the most efficient silo design that is suited to a particular environment. This study was conducted to compare five type of silo namely, Mini Bunker, Well, Siloseal, Plastic Drum and Plastic Bag for corn silage production in Malaysia. The changes in temperature of the silage varied between the silo type with the Mini Bunker showing high temperatures over an extended period compared to the other silo types. The silage in other silo types achieved a stable low temperature within two weeks. When the silo was opened at 61 days almost all silo type had undergone fermentation process as indicated by the low pH. Across the sampling period, the pH generally had increased with the upper portion of the silo having a higher pH due to more exposure to air. In conclusion, based on silage temperature and pH values, Plastic Drum, Plastic Bag and Well silos are recommended.